#### Answer

$\color{blue}{36r^2-60r+25}$

#### Work Step by Step

Use the formula $(a-b)^2=a^2-2ab+b^2$ with $a=6r$ and $b=5$ to obtain:
$=(6r)^2-2(6r)(5)+5^2
\\=\color{blue}{36r^2-60r+25}$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$\color{blue}{36r^2-60r+25}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.